The influence of urban space in dramatic conflicts: transnationality in Mexican fiction films - Silvana Flores (Boletín de la Asociación de Geógrafos Españoles)
Through this article we will analyze a corpus of Mexican fiction films of its classic-industrial period, produced by Pedro and Guillermo Calderón, Palabras de mujer (José Díaz Morales, 1946) and Maternidad imposible (Emilio Gómez Muriel, 1955), that have as a common nexus the interurban transfers, based on the migration phenomenon, the exploitation of a transnational cast and the influences of differentiated urban spaces in the narrative conflicts. Those characteristics will be delineated studying the configuration of urban spaces represented on them, its interference in the dramatic structure of these films and the identity translations presented consequently. The topic of migration and its entailments with the plots of these titles will allow us to elucidate the role awarded to the capital cities as spaces of cultural exchange, as also as essential elements for the achievement of the purposes of their characters, promoting a (des)centralizing vision of those types of territories.